A new blueprint for new digital technology adoption in the mining industry using a systems thinking approach - Fan, Xiang (My University, 2019)
Successful adoption of new technologies is critical for the improvement of efficiency and the enhancement of health and safety in South African mining industry operations. However, the process of new digital technology adoption in the South African mining industry has been slow and difficult. This research is aimed at addressing some of the problems associated with the process. As part of this research, a new blueprint has been developed to guide the commissioning entity through the entire process of new digital technology adoption and installation. The new blueprint will provide capability to monitor the quality of the work during adoption, as well as assessment of the outcome of the adoption by measuring the level of compliance for every activity performed by the commissioning entity during the adoption. The reliability of the new blueprint was verified by assessing the performance of the Wits Mining Institute (WMI) in its installation project of the Schauenburg system. The outcome of the new blueprint verification reveals poor planning and inadequate preparation during the installation of this project. The outcome also indicates that application of the new blueprint will reduce the problems associated with the adoption and speed up new digital technology adoption and its installation for better functionality.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Science in Engineering 2019
Keywords: Technological innovations; Coal mines and mining; Information technology--Economic aspects